2014
DOI: 10.4088/jcp.13m08824
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use and Lifetime History of Mental Disorders in a Community Sample

Abstract: Objectives Past studies have shown that many individuals who use antidepressants do not have a current or lifetime history of mental disorders. However, recent studies suggest that the one-time retrospective evaluation of mental disorders commonly used in such studies may substantially underestimate the true lifetime prevalence of mental disorders. We examined the prevalence of mental disorders, assessed prospectively over multiple interviews, among individuals currently using antidepressants in a community sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In socioeconomic terms, the typical patient taking psychotropic drugs is a woman aged ≥45 years. A significant association has been found between this profile and psychotropic drug use, consistent with findings from studies such as the Baltimore Epidemiologic Catchment Area (ECA) Study [25], which shows ≥45 years to be the age group with the highest prevalence of behavioral disorders in women, or the Swedish Women’s Health in Lund Area Study (WHILA) (Study [26], which was performed to determine the prevalence of psychotropic drug use in middle-aged women and to examine the association with various social factors and health profiles.…”
Section: Discussionsupporting
confidence: 80%
“…In socioeconomic terms, the typical patient taking psychotropic drugs is a woman aged ≥45 years. A significant association has been found between this profile and psychotropic drug use, consistent with findings from studies such as the Baltimore Epidemiologic Catchment Area (ECA) Study [25], which shows ≥45 years to be the age group with the highest prevalence of behavioral disorders in women, or the Swedish Women’s Health in Lund Area Study (WHILA) (Study [26], which was performed to determine the prevalence of psychotropic drug use in middle-aged women and to examine the association with various social factors and health profiles.…”
Section: Discussionsupporting
confidence: 80%
“…2 Finally, visit diagnoses are limited to three, so prescribing without a diagnosis may be overestimated. However, psychotropic use without a diagnosis has been described in other data 6 so is unlikely an artifact of NAMCS.…”
Section: Discussionmentioning
confidence: 83%
“…First, it may reflect expanding use of psychotropic medication beyond that for specific mental health diagnoses: the clinical subpopulation for which use of all medication groups increased was in those without any mental health or pain diagnosis. While prior work has demonstrated use of psychotropic medication in the absence of clearly defined mental disorders, 20,21,4042 this is the first to demonstrate that such use has increased over time in the U.S. In a recent analysis of the Health and Retirement Study, Soldo et al found that, relative to previous cohorts, Baby Boomers approaching retirement reported they have “more difficulty with a range of everyday physical tasks, [but also report] more pain, more chronic conditions, [and] more drinking and psychiatric problems.” 43 In light of this work, a possible interpretation of our results is that newer cohorts of older adults have additional aging-associated distress, leading to increased non-specific use of psychotropic medication in an attempt to address these concerns.…”
Section: Discussionmentioning
confidence: 99%